Penanaman Moral Untuk Meningkatkan Pribadi Berkarakter Remaja - Purwati, Purwati; Yuhenita, Nofi Nur; Purwandari, Septiyati; Faizah, Rayinda (JURKAM: Jurnal Konseling Andi Matappa, 2019)
The purpose of this study is to develop a model of moral cultivation in adolescents in the form of practical books that can be used as a guide for teachers, counselors, parents, students and practitioners based on need assessment problems by involving stakeholders in the preparation and accompaniment. This research is a Research and Development (R&D) research. This research lasted 2 years. In the first year, a study was carried out on a moral inculcation model that had been carried out and a survey of moral behavior in adolescents that became a crucial issue. Furthermore, various models of moral cultivation interventions in adolescents are combined with the values of adolescent karaker values which are priorities for completion. In this study, a qualitative descriptive method was used to collect data while the counseling model for adolescents used the literature review and evaluative methods, so that drafted models and book models of moral cultivation were arranged in adolescents. The moral cultivation model consists of 5 stages namely habituation, observation, example, consequences and coaching.